Potential Simultaneous Aortic and Mitral Valve Endocarditis in A Patient With Bio-Prosthetic Porcine Aortic Valve Replacement and Pacemaker Implantation - Varada, Neilmegh; Quinonez, Jonathan; Sou, Andrew; Chua, Jimmy (Archives of Clinical and Biomedical Research, 2018)
Background Introduction: Endocarditis is an uncommon condition in developed countries. Incidence rates range from 4 to 7 cases per 100,000 individuals a year. The incidence of simultaneous double valve endocarditis is extremely low. Objectives and Aims: This is a case study detailing a 67-year-old Caucasian male who was admitted for suspicion for endocarditis of which Duke Criteria were fulfilled for multi-valve endocarditis. We wish to demonstrate the usefulness of utilizing Duke’s Criteria for management of endocarditis in patients with multivalve involvement. Materials and Methods: Medical records were obtained from Trios Health and Sacred Heart Medical Center after permission was obtained. All documentation and acquired articles were obtained and reviewed. Results: The patient presented to the emergency department complaining of shortness of breath and cough. Evaluation in the emergency department resulted in a suspicion for endocarditis. He was subsequently admitted to the medical floors for management. A transesophageal echocardiogram was conducted, which demonstrated a peri-prosthetic valvular abscess on the aortic valve along with vegetations on the mitral valve. Due to positive Duke criteria for multivalve involvement, he was transferred to a tertiary referral center where he underwent surgery for valve replacement. Surgery noted an abscess with the destruction of the aortomitral continuity but no evidence of infection of the mitral valve. Conclusion: We recommend treatment for multivalve endocardidits when Duke Criteria is satisfied. Our patient may have had a resolution of the abscess prior to surgical intervention, which can be attributed to his vigorous treatment schedule.